2020
DOI: 10.3389/fenrg.2020.584750
|View full text |Cite
|
Sign up to set email alerts
|

Research on Time-Dependent Component Importance Measures Considering State Duration and Common Cause Failure

Abstract: Unlike the current risk monitors, Real-time Online Risk Monitoring and Management Technology is characterized by time-dependent modeling on the state duration of components. Given the real-time plant configuration, it eventually provides the time-dependent risk level and importance measures for operation and maintenance management. This paper focuses on the assessment method of time-dependent importance measures and its risk-informed applications in real-time online risk monitoring and management technology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Xu et al used the values of component importance to investigate a time-dependent risk quantification model, as well as the common cause failure treatment model in operation and maintenance management. The results showed that the absolute values and ranking order of time-dependent importance reflected the effect of the cumulative state duration of component on risk and comprehensively accounted for all possible situations of component unavailability [18]. Kamra and Pahuja analyzed the substation communication network architectures using various reliability importance measures.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al used the values of component importance to investigate a time-dependent risk quantification model, as well as the common cause failure treatment model in operation and maintenance management. The results showed that the absolute values and ranking order of time-dependent importance reflected the effect of the cumulative state duration of component on risk and comprehensively accounted for all possible situations of component unavailability [18]. Kamra and Pahuja analyzed the substation communication network architectures using various reliability importance measures.…”
Section: Introductionmentioning
confidence: 99%